2018
DOI: 10.3847/1538-4357/aabae4
|View full text |Cite
|
Sign up to set email alerts
|

Effective Induction Heating around Strongly Magnetized Stars

Abstract: Planets that are embedded in the changing magnetic fields of their host stars can experience significant induction heating in their interiors caused by the planet's orbital motion. For induction heating to be substantial, the planetary orbit has to be inclined with respect to the stellar rotation and dipole axes. Using WX UMa, for which the rotation and magnetic axes are aligned, as an example, we show that for close-in planets on inclined orbits, induction heating can be stronger than the tidal heating occurr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…For instance, knowing magnetic properties of stars is one of the pieces in the puzzle called stellar activity and includes understanding connections between the magnetic fields, rotation braking, stellar spots, X-ray fluxes, and finally understanding the hazardous environment around planets orbiting these active stars (Vidotto et al 2015;Garraffo et al 2017). Very strong magnetic fields my have even direct impact on the planetary structure by providing additional source of energy via the induction heating (Kislyakova et al 2017(Kislyakova et al , 2018. Especially M dwarfs with dipole dynamo states are interesting objects in this regard because they maintain stable large scale magnetic fields whose energy decay with a separation to the star much slower compared to stars with multipole-dominant fields.…”
Section: Dipole-dominantmentioning
confidence: 99%
“…For instance, knowing magnetic properties of stars is one of the pieces in the puzzle called stellar activity and includes understanding connections between the magnetic fields, rotation braking, stellar spots, X-ray fluxes, and finally understanding the hazardous environment around planets orbiting these active stars (Vidotto et al 2015;Garraffo et al 2017). Very strong magnetic fields my have even direct impact on the planetary structure by providing additional source of energy via the induction heating (Kislyakova et al 2017(Kislyakova et al , 2018. Especially M dwarfs with dipole dynamo states are interesting objects in this regard because they maintain stable large scale magnetic fields whose energy decay with a separation to the star much slower compared to stars with multipole-dominant fields.…”
Section: Dipole-dominantmentioning
confidence: 99%
“…9; Khodachenko et al, 2007). A recent model by Kislyakova et al (2017Kislyakova et al ( , 2018 suggested that some M star habitable zone planets could be strongly affected by electromagnetic induction heating during their early evolution, caused by the star's rotation and the planet's orbital motion. In such a case, induction heating can melt the planetary mantle, hence inducing extreme volcanic activity and constant resurfacing events, similar to Jupiter's moon Io, though this effect would be somewhat smaller for habitable-zone planets.…”
Section: Earth-like Planets In Habitable Zones Of M-and K-type Starsmentioning
confidence: 99%
“…Due to their slow evolution, M stars can keep high levels of XUV radiation in their HZs for a longer time in comparison to solar-like stars (West et al 2008), which can further enhance non-thermal losses. The atmospheres of planets orbiting active low mass M dwarfs may be replenished by extreme volcanic activity due to tidal or induction heating (Driscoll & Barnes 2015;Kislyakova et al 2017Kislyakova et al , 2018. A volcanically active planet would eject gases composed mainly of SO 2 , CO 2 , H 2 O, and S 2 .…”
Section: Atmosphere Parametersmentioning
confidence: 99%